2021
DOI: 10.3390/math9182199
|View full text |Cite
|
Sign up to set email alerts
|

Common Positive Solution of Two Nonlinear Matrix Equations Using Fixed Point Results

Abstract: We discuss a pair of nonlinear matrix equations (NMEs) of the form X=R1+∑i=1kAi*F(X)Ai, X=R2+∑i=1kBi*G(X)Bi, where R1,R2∈P(n), Ai,Bi∈M(n), i=1,⋯,k, and the operators F,G:P(n)→P(n) are continuous in the trace norm. We go through the necessary criteria for a common positive definite solution of the given NME to exist. We develop the concept of a joint Suzuki-implicit type pair of mappings to meet the requirement and achieve certain existence findings under weaker assumptions. Some concrete instances are provided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
2
4
0
1
Order By: Relevance
“…The motivation of this manuscript is to prove the common fixed point theorem for interpolative contraction mappings in bicomplex valued b-metric space. In particular, we generalize and extend the results proved by Beg et al [5], Mani et al [17], Datta et al [7], Nashine et al [20] and Joseph et al [12].…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation
“…The motivation of this manuscript is to prove the common fixed point theorem for interpolative contraction mappings in bicomplex valued b-metric space. In particular, we generalize and extend the results proved by Beg et al [5], Mani et al [17], Datta et al [7], Nashine et al [20] and Joseph et al [12].…”
Section: Introductionsupporting
confidence: 86%
“…Recently, the study of nonlinear matrix equations was given by Garai and Dey [9] gave a common solution to a pair of non-linear matrix equations via fixed point results. Nashine et al [20] proved a common positive solution of two nonlinear matrix equations using fixed point Results. Joseph et al [12] gave the results by solving a system of linear equations via bicomplex valued metric space.…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript aims to prove some common fixed point theorems for interpolative contraction mappings in bicomplex valued b-metric spaces. In particular, we generalize and extend the results proved by Beg et al [5], Mani et al [23], Datta et al [9], Nashine et al [26] and Joseph et al [14].…”
Section: Introductionsupporting
confidence: 86%
“…Recently, the study of nonlinear matrix equations was given by Garai and Dey [11] who gave a common solution to a pair of non-linear matrix equations via fixed point results. Nashine et al [26] found a common positive solution of two nonlinear matrix equations using fixed point Results. Joseph et al [14] gave some results by solving a system of linear equations via a bicomplex valued metric.…”
Section: Introductionmentioning
confidence: 99%
“…It has been extended and generalized in numerous directions (for the detail, see [16][17][18]). We suggest the reader to see [19][20][21] for further information on fixed point theory and its applications in various spaces.…”
Section: Mathematical Modeling Of the Two-armed Bandit Experimentsmentioning
confidence: 99%